Kajian Kestabilan Lereng RKAP 2018 Lokasi Penambangan Muara Tiga Besar Utara PT. Bukit Asam Tbk Tanjung Enim Sumatera Selatan - Muhammad Irawan; Bambang Heriyadi; Adree Octova (Journals Mining Engineering : Bina Tambang, 2018)
Abstract. This research was carried out at MTBU pit mining PT. Bukit Asam Tbk. With the occurrence of landslides on the cross section of Y-Y 'low wall elevation +74 to +62 in the pit area of MTBU PT. Bukit Asam Tbk, it is necessary to do geotechnical studies so that the mining plan can be supported with accurate data, especially in terms of slope stability. To get the optimum geometry recommendations, as well as safety factors (FK) that are in accordance with the plan, we get the initial data Silty Claystone: Content weight (γ) = 22,19 kN / m3, cohesion (c ') = 28,14 kN / m2 and inner sliding angle (ϕ ') = 33,30 °. Silty Sandstone: content weight (γ) = 20.36 kN / m3, cohesion (c ') = 26,38 kN / m2 and inner sliding angle (ϕ') = 25,50 °. Sandy Silt: Contents weight (γ) = 19.67 kN / m3, cohesion (c ') = 32,16 kN / m2 and inner sliding angle (ϕ') = 39,11 °. Recommendation slope geometry: 1. Morgenstren-Price method based on the design results using the Geostudio Slope / W 2007 program, for each section both single slope and overall slope safety factor ≥ 1,25 which means that it is stable or safe. 2. The Hoek and Bray method, 1981 carried out an analysis of the back slope of the single slope high wall elevation +74 to +62 when a landslide occurred using material input properties. After analyzing the slope stability with the analysis parameters behind Hoek & Bray (FK = 0,99), the value (FK = 0.919) is obtained. In saturated conditions, handling is needed to make the slope more gentle where the slope angle is 23,77o with the same height 12 m, so that the value (FK = 1,288) is obtained.Keywords: Slope Stability, Back Analysis, Safety Factor, Slope Geometri, Input PropertiesAbstract.This research was carried out at MTBU pit mining PT. Bukit Asam Tbk. With the occurrence of landslides on the cross section of Y-Y 'low wall elevation +74 to +62 in the pit area of MTBU PT. Bukit Asam Tbk, it is necessary to do geotechnical studies so that the mining plan can be supported with accurate data, especially in terms of slope stability. To get the optimum geometry recommendations, as well as safety factors (FK) that are in accordance with the plan, we get the initial data Silty Claystone: Content weight (γ) = 22,19 kN / m3, cohesion (c ') = 28,14 kN / m2 and inner sliding angle (ϕ ') = 33,30 °. Silty Sandstone: content weight (γ) = 20.36 kN / m3, cohesion (c ') = 26,38 kN / m2 and inner sliding angle (ϕ') = 25,50 °. Sandy Silt: Contents weight (γ) = 19.67 kN / m3, cohesion (c ') = 32,16 kN / m2 and inner sliding angle (ϕ') = 39,11 °. Recommendation slope geometry: 1. Morgenstren-Price method based on the design results using the Geostudio Slope / W 2007 program, for each section both single slope and overall slope safety factor ≥ 1,25 which means that it is stable or safe. 2. The Hoek and Bray method, 1981 carried out an analysis of the back slope of the single slope high wall elevation +74 to +62 when a landslide occurred using material input properties. After analyzing the slope stability with the analysis parameters behind Hoek & Bray (FK = 0,99), the value (FK = 0.919) is obtained. In saturated conditions, handling is needed to make the slope more gentle where the slope angle is 23,77o with the same height 12 m, so that the value (FK = 1,288) is obtained.Keywords:  Slope Stability, Back Analysis, Safety Factor, Slope Geometri, Input Properties